Microstructure, and mechanical and thermal properties of CuSn/FeCrp metal matrix composites processed by powder metallurgy - Yilmaz, O; Turhan, H (Maney Publishing, 2002)
The effects of FeCr particulates (FeCrP) on microstructure, and thermal and mechanical properties of powder metallurgy Cu-Sn metal matrix composites were investigated using scanning electron microscopy, energy dispersive spectrometry, X-ray diffraction, differential thermal analysis, low cycle fatigue testing, hardness measurements, and Charpy V notch impact testing. Carbides of type M23C6 and M7C3 were precipitated around the FeCrP in the matrix of the alpha-Cu-Sn structure. Hence, hardness, fatigue life, tensile strength, and the grain coarsening temperature of the Cu-Sn alloy increased and the toughness of the samples decreased The electrical resistivity of sintered specimens was measured in the temperature interval 298-328 K, and in this temperature interval it was seen that the FeCrP increased electrical and thermal resistance.
Keywords: Reinforced Aluminum; Wear Behavior; Sliding Wear; Stainless; Steel; Alloy